The Correlation Between the Size, Independence and Experience of Internal Audit and its Impact on Reducing Financial Corruption: Evidence from the Public Sector in Iraq - Wahhab, Asaad; Al Saadi , Farqad Mohammed Bakr (Technium Social Sciences Journal, 2024)
Financial corruption crimes in the public sector are prevalent in numerous developing nations, frequently stemming from political, economic, or social problems, among other things. In order to combat these unethical behaviours in the public sector, governments are aggressively striving to improve the internal audit function. This requires recruiting an adequate number of auditors who can carry out their duties with the highest level of professionalism, fostering the autonomy of the audit function and auditors, and improving the effectiveness of auditors through training, qualifications, and education. In the end, this will help decrease the financial corruption that hinders the long-term progress of Iraq. The goal of this study is to assess the magnitude, autonomy, and expertise of internal auditing in Iraq's public sector entities, as well as the extent of financial corruption within this sector. To accomplish the goals of the study, we created a survey and administered it to a randomly selected group of internal auditors in 15 Iraqi governorates, excluding the Kurdistan Region. We issued a total of 174 questionnaires, each containing two axes. The initial segment has three facets of internal auditing (magnitude, autonomy, and expertise) and a total of 27 inquiries. The second axis consisted of 14 questions that assessed financial corruption using regression analysis. The study used basic and numerous linear tests to investigate the hypotheses, ultimately determining that the inclusion of more staff was essential for carrying out certain audit responsibilities. The department lacks a proportional allocation of internal auditors compared to the workload, resulting in the audit body's weak independence. This is primarily due to the administration's interference in the transfer and employment of individuals based on its own discretion, as well as corruption prevalent in government units, particularly in investment spending. The results also revealed a direct relationship between size, independence, internal auditing experience, and financial corruption.